Anthropological Approaches to Human Nature, Cultural Relativism and Ethnocentrism: Part 4: The Human in Culture - Darnell, Regna (Anthropologica, 2022)
This article reflects on how anthropology has traditionally dealt with the alternation of cultural specificities and human universals. It revisits the foundational anthropological concept of cultural relativism in light of the inevitability of standpoint and ethnocentrism. Today, within the discipline of anthropology, it is possible, indeed necessary, to update the conceptual apparatus in order to maintain the potential to speak truth to power and to undertake a cross-culturally sophisticated critique of globalization as we once did of evolution. The methods and messages of anthropology remain crucial to contemporary practice of the discipline in Canada and elsewhere